Distortion of optical feedback signals in microchip Nd：YAG lasers subjected to external multi-beam interference feedback - 谈宜东 张书练 任舟 任成 张亦男 (Chinese physics B, 2010)
This paper proposes a theoretical analysis for the characteristics of an external cavity Nd：YAG laser with feedback of multiple-beam interference, which is induced by the multi-reentrance of the light from the external Fabry-Perot cavity. The theoretical model considers the multiple beam interference of the external Fabry-Perot cavity. It is found that the optical feedback signals are distorted to pulse waveforms instead of the sinusoidal ones in conventional feedback. The experimental results are in good agreement with the theoretical analysis. The obtained theoretical and experimental results can advance the development of a laser feedback interferometer.